Museum audio description - Martins, Cláudia (2011)
Audio description for the blind and visually impaired has been around since people have described what is seen. Throughout time, it has evolved and developed within different media, starting with reality and daily life, moving into the cinema and television, then across other performing arts, museums and art galleries, and public places. Thus, academics and entertainment providers have developed a growing interest for audio description, especially in what concerns the best methods and strategies to make words/texts give life to visual texts. The motto is to “make images verbal” or, within museum contexts, to make art (and not only) come alive for those who do not actually see. To them enjoyment might mean to see things through words. This presentation will focus on this particular form of intersemiotic translation.